SANKSI PIDANA BAGI DEMONSTRAN YANG ANARKIS - Rizky Asydiqy Asydiqy; Fikrotul Jadidah Jadidah (Gorontalo Law Review, 2022)
Basically, demonstration is a form of expression from a group of people that contains demands for circumstances, reality, an overflow of awareness and even a form of critical national education. Regarding demonstrations without anarchy, in addition to improving the public service system, there needs to be awareness and control from the demonstrators as well as mutual understanding from the police security so that no party feels disadvantaged and even becomes a victim of riots. According to the provisions of Article 1 of Law Number 9 of 1998 concerning Freedom of Expressing Opinions in Public, which What is meant by freedom of expression is the right of every citizen to express his thoughts orally, in writing, and so on freely and responsibly in accordance with the provisions of the applicable laws and regulations.